2
$\begingroup$

Let $g$ be a Lie algebra and $U(g)$ its enveloping algebra. I think that $U(g)$ is a Poisson algebra where the Poisson bracket is given by the Lie bracket of $g$ and Leibniz rule. Is this true? Thank you very much.

$\endgroup$
  • $\begingroup$ Yes, see here. The tensor algebra $T(L)$ of a Lie algebra $L$ is a Poisson algebra, and $U(L)=T(L)/I$, where $I$ is the two-sided ideal over $T(L)$ generated by elements of the form $ a ⊗ b − b ⊗ a − [ a , b ]$. $\endgroup$ – Dietrich Burde Feb 28 '17 at 15:18
  • $\begingroup$ @DietrichBurde, thank you very much. Is $I$ a Poisson ideal of $T(L)$: $\{I, T(L)\} \subset I$? $\endgroup$ – LJR Feb 28 '17 at 15:22
  • $\begingroup$ May be an easier proof is given in Example $2.3$ here. $\endgroup$ – Dietrich Burde Feb 28 '17 at 15:33
  • $\begingroup$ @DietrichBurde, thank you very much. $\endgroup$ – LJR Feb 28 '17 at 15:41
  • $\begingroup$ @DietrichBurde, I verified that $I$ is a Poisson ideal of $T(L)$. Let $I'=\{ab-ba-[a,b]\}$ (I omitted the tensor notation). Then $I=T(L)I'T(L)$. It suffices to verify that for all $x \in I'$, $h, h', c \in T(L)$, we have $\{hxh', c\} \in I$. According to the article, the Poisson bracket defined on $T(V)$ is given by \begin{align} \{d,e\}=[d,e], d, e \in L, \end{align} and Leibniz rule. We have \begin{align} \{hxh',c\} = [hxh',c]=hx[h',c]+[h,c]xh'+h[x,c]h'. \end{align} This is in $I$ if $[x,c] \in I'$. $\endgroup$ – LJR Feb 28 '17 at 16:07
2
$\begingroup$

$T(g)$ is a Poisson algebra under the bracket given by $\{a,b\}=[a,b], a, b \in g$ and Leibniz rule: \begin{align} \{ab,c\} = a\{b,c\}+\{a,c\}b, \ a, b, c \in T(g). \end{align} To prove that $U(g)=T(g)/I$ is Poisson, we need to verify that $I$ is a Poisson ideal of $T(g)$. Let $I′=Span_{\mathbb{C}}\{ab−ba−[a,b]: a, b \in g\}$. Then $I=T(g)I′T(g)$. It suffices to verify that for all $x=ab-ba-[a,b]$, $a,b \in g$, $h,h′,c \in T(L)$, we have $\{hxh′,c\} \in I$.

We have \begin{align} \{hxh′,c\}=\{hxh′,c\}=hx\{h′,c\}+\{h,c\}xh′+h\{x,c\}h′. \end{align} This is in $I$ if $\{x,c\} \in I′$.

We have \begin{align} \{x,c\}&=\{ab−ba−[a,b],c\}\\ & = \{ab,c\}-\{ba,c\}-\{[a,b],c\} \\ &=a\{b,c\}+\{a,c\}b−b\{a,c\}−\{b,c\}a−\{[a,b],c\}. \end{align} Since $a,b,c,[a,b] \in g$, we have \begin{align} \{x,c\} &=a\{b,c\}+\{a,c\}b−b\{a,c\}−\{b,c\}a−\{[a,b],c\} \\ &=a[b,c]+[a,c]b−b[a,c]−[b,c]a−[[a,b],c] \\ &=([a,c]b−b[a,c]−[[a,c],b])+(a[b,c]−[b,c]a−[a,[b,c]])+[[a,c],b]+[a,[b,c]]−[[a,b],c]\\ &=([a,c]b−b[a,c]−[[a,c],b])+(a[b,c]−[b,c]a−[a,[b,c]]) \in I′. \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.